2009
DOI: 10.1029/2009gl041081
|View full text |Cite
|
Sign up to set email alerts
|

Depth dependent seismic scattering attenuation in the Nuevo Cuyo region (southern central Andes)

Abstract: [1] In the present work we separated intrinsic from scattering attenuation coefficients both for the crust and the upper mantle in the tectonically highly active areas of the Southern-Central Andes -Nuevo Cuyo region, analyzing two groups of earthquakes, well separated in depth. This region is characterized by the presence of flat subduction. We apply MLTWA (Multiple Lapse Time Window Analysis), coda normalization and Q-coda techniques to measure the scattering and intrinsic attenuation coefficient and the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 10 publications
(16 reference statements)
3
10
0
Order By: Relevance
“…Son focal depth, around 10 km, than those of the other studies. The same explanation is applicable to the observations at southern-central Andes (Badi et al, 2009), which showed higher Q −1 values at 3-6 Hz for shallow crustal events than those of deep upper-mantle events. This difference was more significant for Q −1 S values.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Son focal depth, around 10 km, than those of the other studies. The same explanation is applicable to the observations at southern-central Andes (Badi et al, 2009), which showed higher Q −1 values at 3-6 Hz for shallow crustal events than those of deep upper-mantle events. This difference was more significant for Q −1 S values.…”
Section: Resultssupporting
confidence: 55%
“…In addition, different focal depth of each earthquake may cause significant scatter because large variations of Q −1 values of S waves are well known in the crust and upper mantle (Mitchell and Xie, 1994;Mitchell, 1995). In spite of the large difference in the Q values according to the depth, only a few of the previously reported MLTWA studies have considered between the shallow crust and the upper-mantle source (Badi et al, 2009). Recently, our review on MLTWA, where the focal depth range was narrowed around 10 km in South Korea (hereafter S. Korea), showed remarkably different attenuation values (Chung and Asep, 2013) compared to those of the other studies Chung, 2014) that used various focal depths.…”
Section: Introductionmentioning
confidence: 97%
“…For shallow events, they found approximately Q 0 100 and Q 10 1300 while we found values of 149 and 772, respectively. Few parameters were given by Badi et al (2009); however, the lapse time was 90 s, substantially longer than the 30 s we use, and one could therefore expect a higher Q as also observed for Q 10 . There was no obvious division to make in the Shanxi rift system and due to the relatively large distance between stations in the network, only a few results were obtained when using a lapse time of 30 s and all data were grouped together.…”
Section: Northwestern and Central Argentinamentioning
confidence: 85%
“…Because the difference was small, the two groups were merged. Badi et al (2009) studied Q from both shallow and deep events in the southern part of our study area using different methods, among these CWD. For shallow events, they found approximately Q 0 100 and Q 10 1300 while we found values of 149 and 772, respectively.…”
Section: Northwestern and Central Argentinamentioning
confidence: 99%
“…In the 2 4 Hz band, scattering is strong in Hokkaido and northern Honshu, but it is weak in western Japan, and especially weak in Shikoku. 1 Kanto-Tokai, Japan (Fehler et al 1992), 2 Long Valley, California (Mayeda et al 1992), 3 Central California (Mayeda et al 1992), 4 Hawaii (Mayeda et al 1992), 5 Japan (Hoshiba 1993), 6 Southern California (Jin et al 1994), 7 Northern Greece (Hatzidimitriou 1994), 8 Southern Spain, < 170 km (Akinci et al 1995), 9 Southern California (Adams and Abercrombie 1998), 10 Northeastern Venezuela (Ugalde et al 1998), 11 Eastern Turkey (Akinci andEyidogan 2000), 12 Southern Apennines Bianco et al (2002), 13 South Central Alaska (Dutta et al 2004), 14 Southern Netherlands (Goutbeek et al 2004), 15 Northeastern Colombia (Vargas et al 2004), 16 Northeastern Italy (Bianco et al 2005), 17 Southern Sicily (Giampiccolo et al 2006), 18 Southern Anatolia (Sahin et al 2007), 19 Japan (average) (Carcolé and Sato 2010), 20 Southern central Andes (D <40 km) (Badi et al 2009), 21 Southern central Andes (40 km < D < 210 km) (Badi et al 2009), 22 Southeastern South Korea (Lee et al 2010) In the 8 16 Hz band, scattering is strong in Honshu; however, it is weak in Shikoku.…”
Section: Mltwa In Japanmentioning
confidence: 99%